Let the variables be c and a.
c+a = 275 (people)
($3/child)(c) + ($6.40/adult)(a) = $1284
Solve c+a = 275 for c and subst. the result into the other equation, to eliminate the variable c:
c = 275-a
Then 3(275-a) +6.40(a) = 1284, or 825 - 3a + 6.40a = 1284
Combining like terms: 9.40a = 459. Then, a = 459/9.40 = 48.83
This makes no sense. I've checked these calculations for errors twice. Would you please go back and ensure that you have copied down the original problem completely and accurately? Thanks.
combining like terms, we get 459 = 9.40a. Solving for a: a = 459/9.40 =